Quality Evaluation of Saposhnikovia divaricata (Turcz.) Schischk from Different Origins Based on HPLC Fingerprint and Chemometrics - Yuqiu Chen; Zhefeng Xu; Siying Gao; Tao Zhang; Changbao Chen (Journal of Chemistry)
A valid and encyclopedic evaluation method for assessing the quality of Saposhnikovia divaricata has been set up based on the analysis of a high-performance liquid chromatography (HPLC) fingerprint combined with the cluster analysis (CA), principal component analysis (PCA), partial least square discriminant analysis (PLS-DA), and similarity analysis. 15 peaks of the common model were obtained and used for the similarity analysis, CA analysis, PCA analysis, and PLS-DA analysis. The fingerprint of S. divaricata was established, and 15 common peaks were calibrated. The four common peaks were identified as prim-o-glucosylcimifugin, 4-O-β-D-glucosyl-5-O-methylvisamminol, cimifugin, and sec-o-glucosylhamaudol by comparison with the reference substance. The similarity of the fingerprints of the 33 batches of S. divaricata is above 0.9. Cluster analysis divides the 33 batches of S. divaricata into 2 categories. Principal component analysis (PCA) roughly divides them into 4 categories. Partial least squares method-discriminant analysis (PLS-DA) screened to obtain 2 differential markers, the different components were designated by the reference substance as 4-O-β-D-glucosyl-5-O-methylvisamminol and cimifugin. The fingerprint established by this study combined with chemometrics analysis is reasonable, effective, accurate, and simple, which makes the information more comprehensive and can provide a scientific basis and reference for quality control and quality evaluation of S. divaricata.